Transfer effects on training the refraction of light when hitting the target in the water - Nešić, Blagoje V. (Collection of Papers of the Faculty of Philosophy in Priština, 2014)
This paper presents experimental research of the effects of training students in the principles of light refraction to succeed in hitting the target in the water. The aim of this experiment was to investigate the veracity of the conclusions reached by Judd in 1908, since this experiment has been crucial in educational psychology - it represents the experimental basis of the generalized theory of transfers. Namely, Judd demonstrated that general experience (not identical elements) is transferred in the process of transfer. There were two groups in the research: the experimental and the control group. The following variables were controlled: hitting the target in the air; the knowledge of the refraction of light, age, gender, and number. Unlike the control group, the experimental group received training in the principles of light reflection. Having completed the training of the experimental group, the hitting of the target in the water was performed, firstly at the depth of 50 cm and then at the depth of 20 cm. The sample included two classes of eighth - grade students from the elementary school in Pečenjevac (the experimental group) and Razgojna (the control group). The research was conducted at the beginning of the school year (1975/76). In the process, there were errors in hitting the target. For the processing of data, the analyses of variance and measures of statistical descriptions have shown the following: 1) the success of the experimental group in hitting the targets at the first depth of water is significantly better than the success of the control group F (1,102) = 5.240 , p <0.05; 2) the experimental group has achieved significantly better results than the control group when hitting the targets at the altered depth of water F (1,102) = 27.767 , p <0.01); 3) when comparing the progresses of groups or differences of differences showed that the experimental group was significantly better than the control group F (1,192)=9,5300, p<0.01). Even though this experiment differs from Judd’s experiment in terms of methodology, it essentially confirms his findings.